The logic of illegal neighborhood inhabitants in order to achieve urban integration and alleviate urban marginalization, a case study of the city of Constantine. - Hamoui, Abdelhadi (Journal of Human Sciences, 2021)
The revival of illegal housing in the city of Constantine has become synonymous with various manifestations and forms of urban isolation and marginalization that are reflected in the exclusion of people living in difficult social and economic conditions from society and the city and. This article aims to study the logic of residents of illegal neighborhoods in the city of Constantine in order to integrate themselves with the rest of society and the city. In order to achieve this, we will try to identify the methods used by the population with a view to obtaining a place within the community and the city, as well as the factors used to obtain official recognition by the authorities and to obtain different financial incomes, since the logic of urban integration followed by the population is not indiscriminate but generally follows a number of methodological steps and possesses a variety of social and economic aspects.